KAMPANYE PEMILAHAN LIMBAH RUMAH TANGGA DI KELURAHAN SUKAMAJU KECAMATAN SAKO PALEMBANG - B. Santoso; Y. Mahdiana; Ibrahim ,; Lisdiana . (Buletin Udayana Mengabdi, 2021)
Garbage is used good that can cause environmental damage and threaten the sustainability of living things’ ecosystems. Waste that is not well-managed will turn into toxic compounds and will be harmful to health. Yet, if it handled properly, it can provide economic benefits. Waste management is not only the responsibility of the government but also the community. The purpose of this campaign activity was to change the mindset and behavior of the people in Sukamaju Village, Palembang in handling their household wastes, especially related to the sorting of organic and inorganic waste. Campaign activities were carried through 4 stages, namely, observation, socialization, providing assistance, and monitoring-evaluation. In general, the residents of Sukamaju urban village had finally realized that household wastes should have been sorted by their types. However, the results of the monitoring showed that the assistance for the trailer trash cans provided by the service team had not been used properly. Therefore, campaign activities should ideally be carried out periodically and continuously accompanied by other efforts in the form of creating a waste bank and training skills to process garbage into goods that have economic value.